Comparison of definitive-intent finely fractionated and palliative-intent coarsely fractionated radiotherapy as adjuvant treatment of feline microscopic injection-site sarcoma. Issue 2 (February 2019) - Rossi, Federica; Marconato, Laura; Sabattini, Silvia; Cancedda, Simona; Laganga, Paola; Leone, Vito F; Rohrer Bley, Carla
Objectives: The aim of this retrospective, bi-institutional study was to evaluate the progression-free interval in a cohort of cats with postoperative microscopic injection-site sarcoma (ISS) treated with two different radiotherapy protocols. Methods: Included in the study were cats with ISSs undergoing macroscopic surgical removal and subsequent electron beam radiotherapy treatment with either a finely fractionated protocol (48 or 52.8 Gy over 4 weeks delivered in 12 or 16 fractions) or a coarsely fractionated protocol (36 Gy over 3 weeks administered in six fractions). Medical records were reviewed and follow-up information was collected. The Kaplan–Meier method and log-rank test were used to compare the progression-free interval (PFI) between the two protocols and to test the influence of many clinical variables. Results: Fifty-nine cats were included; 38 underwent a finely fractionated protocol and 21 a coarsely fractionated protocol. PFI was not significantly different between the two groups. Overall PFI was 2000 days (2000 vs 540 days; P = 0.449). When only first-occurrence cases were included, median PFI was significantly longer in the finely fractionated group compared with the coarsely fractionated group (1430 vs 540 days; P = 0.007). In cats that underwent multiple surgeries PFI was not different between protocols (233 vs 395 days; P = 0.353). Conclusions and relevance: Cats with first-occurrence ISSs appear to benefit from postoperative finely fractionated radiotherapy. The same benefit was not evident in cats that underwent multiple surgeries and we think a coarsely fractionated protocol would be indicated in these cases.